Evaluation of apical microleakage of teeth sealed with four different root canal sealers Avaliação da microinfiltração apical em dentes obturados com quatro diferentes cimentos endodônticos - Fábio Dultra; Juliana Machado Barroso; Laise Daniela Carrasco; Alexandre Capelli; Danilo M. Zanello Guerisoli; Jesus Djalma Pécora (University of São Paulo, 2006)
OBJECTIVES: to compare the apical sealing ability of four root canal sealers. MATERIAL AND METHODS: forty extracted human maxillary canines were instrumented 1 mm short of the anatomical apex and randomly assigned to four groups (n=10), according to the root canal sealer used for obturation: Endofill, AH Plus, EndoREZ and Epiphany. Root canals were obturated with gutta-percha points, except for the Epiphany group, in which resin points (Resilon) were used. The teeth were immersed in India ink for seven days and clarified using methyl salicylate. The extent of apical dye penetration was measured with a measuroscope in all aspects of the canal. RESULTS: AH Plus (0.02 mm ± 0.07), Epiphany (0.00 mm ± 0.00) and EndoREZ (0.32 mm ± 0.62) did not differ statistically to each other (p>0.01). EndoFill presented the highest dye penetration mean (0.83 mm ± 0.73) and was statistically different from the other sealers (p<0.01). CONCLUSION: the resin-based root canal sealers presented lesser apical microleakage than the zinc oxide and eugenol based sealer. No statistical differences were observed among resin based sealers. OBJETIVOS: comparar a capacidade de selamento apical de quatro cimentos endodônticos. MÉTODOS: quarenta caninos superiores humanos extraídos foram instrumentados 1 mm aquém do ápice anatômico e distribuídos aleatoriamente em quatro grupos (n=10), de acordo com o cimento endodôntico utilizado para a obturação: Endofill, AH Plus, EndoREZ e Epiphany. Os canais radiculares foram obturados pela técnica da condensação lateral com os cimentos e com cones de guta-percha, exceto o grupo do Epiphany, no qual os cones de resina (Resilon) foram utilizados. Os dentes foram imersos em nanquim por sete dias e submetidos ao processo de diafanização e, então, clarificados empregando-se o salicilato de metila. A extensão de penetração via apical do corante foi medida por meio de um microscópio de mensuração em todas as faces do terço apical. RESULTADOS: AH Plus (0,02 mm ± 0,07), Epiphany (0,00 mm ± 0,00) e EndoREZ (0,32 mm ± 0,62) não diferiram estatisticamente entre si (p>0,01). EndoFill apresentou a maior média de penetração do corante (0,83 mm ± 0,73) e diferiu estatisticamente dos demais (p<0,01). CONCLUSÕES: os três cimentos resinosos apresentaram menor microinfiltração que o cimento à base de óxido de zinco e eugenol, porém, promoveram selamento apical semelhante entre si.